Ninetails : nine tales - Mao, Sally Wen (Penguin Books, 2024)
"A "smart and deft" fabulist debut collection of stories re-imagining the nine-tailed fox spirit of Asian folklore (C. Pam Zhang). A fox spirit avenges a teen girl by seducing her abuser. A shapeshifting woman finds herself chased through the woods by fox hunters; meanwhile, an assassination plot called Operation Fox Hunt unfolds against the last Queen of Korea. Chinese migrants hoping to make new lives as "paper children" in America find their pasts--and their hopes for the future--embodied in the foxes that haunt the harbor in 1900s Angel Island. In the nine tales of Ninetails, acclaimed poet Sally Wen Mao reimagines the fox spirit from Asian folklore--a shapeshifter, shaman, and seductress--as an icon of vengeance, solidarity and liberation. The characters of her stories are varied--from silicone sex dolls who come to life with new purpose, to women whose crushes manifest as stones--but they all reach for a common purpose: to find truth and belonging in a difficult world determined to consider them alien. With the fabulist vibrancy of Carmen Maria Machado, the sinuous world-building of Helen Oyeyemi, and the sensuous feminist rage of Han Kang, Ninetails is both timeless--unearthing a cultural icon whose origins date back over a thousand years--and timely in its contemporary political urgency"--